Okay, let's start by finding a value of x in terms of y. That will be like x=something with a y in it. That way we can "plug in" the value of x into the other equation and get a result for y. Then we can find x. Let's start. The second equation looks easier to solve for x because you don't have to divide anything.
x-2y=-3
Add 2y to both sides
x=2y-3
Now plug 2y-3 in for x in the first equation, and we get
2x+3y=8
2(2y-3)+3y=8
Use distributive property, simplify
4y-6+3y=8
Combine like terms.
7y-6=8
Add 6 to both sides
7y=14
Divide both sides by 7
y=2
We now have a value for y. Let's plug it into one of the equations:
x-2y=-3
x-2(2)=-3
Simplify and solve
x-4=-3
x=-3+4
x=1
x=1
y=2
That is your answer.
Hope this helps.
2006-11-28 04:55:12
·
answer #1
·
answered by Aegor R 4
·
0⤊
1⤋
2x + 3y = 8 - - - - - - -Equation 1
x - 2y = - 3- - - - - - - Equation 2
- - - - - - - -
Substitute Method equation 2
x -2y = - 3
x - 2y + 2y = - 3
x = - 3 + 2y
Insert the x value into equation 1
- - - - - - - - - - - - - -
2x + 3y = 8
2(- 3 + 2y) + 3y = 8
- 6 + 4y +3y = 8
- 6 + 7y = 8
- 6 + 7y + 6 = 8 + 6
7y = 14
7y/7 = 14/7
y = 2
The answer is y = 2
Insert the y value into equation 2
- - - - - - - - - - - - - - - - - - - - - --
x - 2y = - 3
x - 2(2) = - 3
x - 4 = - 4
x - 4 + 4 = - 4 + 4
x = 1
The answer is x = 1
Insert the x value into equation 2
- - - - - - - - - - - - - - - - - - - - - - -
Check for equation 2
x - 2y = - 3
1 - 2(2) = - 3
1 - 4 = - 3
-3 = - 3
- - - - - - - -
Check for equation 1
2x + 3y = 8
2(1) + 3(2) = 8
2 + 6 = 8
8 = 8
- - - - - - - - - - -
The solution set is { 1, 2 }
- - - - - -s-
2006-11-28 14:14:02
·
answer #2
·
answered by SAMUEL D 7
·
0⤊
0⤋
x - 2y = -3
x = 2y - 3
2x + 3y = 8
2(2y-3) + 3y = 8 (substituting 2y-3 in for x)
4y - 6 + 3y = 8
7y - 6 = 8
7y = 14
y = 2
x = 2y-3 = 2(2)-3 = 1
2006-11-28 13:12:39
·
answer #3
·
answered by Kyrix 6
·
0⤊
0⤋
2x + 3y = 8
AND
x - 2y = -3
First, take and solve for x:
x - 2y = -3
x = -3 + 2y
Second, plug this into the first equation to solve for y.
2x + 3y = 8
2(-3 + 2y) + 3y = 8
-6 + 4y + 3y = 8
7y = 14
y = 2
Third, take this value of y and plug it into either one of the formulas to solve for x.
2x + 3y = 8
2x + 3(2) = 8
2x + 6 = 8
2x = 2
x = 1
Or...
x - 2y = -3
x - 2(2) = -3
x - 4 = -3
x = 1
x = 1
y = 2
Hope this helps!
**Note: Aegor R decided to edit his answer (that had absolutely no work, mind you) after everyone else took their time to respond to your question completely.
2006-11-28 12:56:11
·
answer #4
·
answered by sft2hrdtco 4
·
0⤊
0⤋
2x+3y=8
x-2y=-3
Multiply 2nd equation by -2 getting
-2x +4y= 6
Now add this new equation to the 1st equation getting
7y=14
y=2
Now plug y = 2 into the second equation getting;
x-(2)(2)=-3
x-4=-3
x=1
2006-11-28 13:00:59
·
answer #5
·
answered by ironduke8159 7
·
0⤊
0⤋
2x+3y=8
2x-4y=-6 (2)*2
subtracting
7y=14
y=2
substituting
2x+6=8
2x=2
x=1
2006-11-28 12:57:21
·
answer #6
·
answered by raj 7
·
0⤊
0⤋
2x + 3y = 8
-( x - 2y = -3)*2
---------------------
0x + 7y = 14
so, y = 2
Then:
2x + 3(2) = 8
=> 2x = 2
=> x=1
2006-11-28 12:56:46
·
answer #7
·
answered by zotiskk 1
·
0⤊
0⤋